Movin' on up: Hierarchical occupational segmentation and gender wage gaps - Dina Shatnawi; Ronald L. Oaxaca; Michael R. Ransom (Institute for the Study of Labor (IZA), 2012)
Our study evaluates and extends existing wage decomposition methodologies that seek to measure the contributions of endowments, pure wage discrimination, and job segregation. Of particular interest is the model of hierarchical segregation in Baldwin, Butler, and Johnson (2001). We employ data from a regional supermarket that faced a Title VII class-action lawsuit to examine how standard wage specifications integrated with a model of hierarchical segregation might perform in wage decompositions. Our results show that a common misspecification of the wage structure leads to false inferences about the presence of pure wage discrimination. We demonstrate the generalizability of our methodology using CPS data.
Keywords: J71; 330; gender discrimination; job segregation; wage decompositions; Lohndifferenzierung; Geschlechterdiskriminierung; Arbeitsmarktdiskriminierung; SB-Lebensmittelgeschäft; USA